Electrical Cardioversion in Atrial Fibrillation: Success Rates - Uzma Gul , Azmat Hayat (Journal of Rawalpindi Medical College, 2018)
Background: To study the immediate and long term success of Direct Current (DC) Cardioversion for persistent non-valvular atrial fibrillation. Methods: In this prospective study 200 patients with persistent non-valvular atrial fibrillation presenting to arrhythmia clinics were selected. They were anticoagulated to INR of 2-3, a transesophageal echocardiogram was performed 3 weeks later to rule out left atrial thrombus and then patients were subjected to external electrical cardioversion. Patients were followed up 3 monthly for a total period of 3 years to assess maintenance of sinus rhythm. Results: The mean age of study population was 69 years and 65.5% were male. Immediate success was achieved in 65.5% patients. At 3 months 54.5% were in sinus rhythm and this percentage dropped to 43.5% at 6 months.185 patients completed 1 year follow up and 28.5% were found to be in sinus rhythm. At 2 years 172 patients reported out of which 19.50% were still in sinus rhythm. In relation to the LA size immediate success was achieved in 58.01% with size less than 4cm, 35.11% with LA size between 4 to 4.5cm and only in 6.8% with LA size greater than 4.5cm. This trend was maintained in long term as well. And in relation to drugs those on amiodarone had best success. Complications were encountered in two patients, one patient had transient ischemic attack and other suffered bradycardia needing temporary pacing. Conclusion: DC cardioversion for rhythm control in atrial fibrillation is a safe and effective treatment strategy with reasonable short term success and although limited but meaningful long term success.